The Fiscal and Economic Effects of Federal Credit Assistance Programs. (IMF Working Papers; Working Paper, 1990)
While federal credit programs are varied in form, their fiscal and economic effects arise primarily from the same source-each program's subsidy component. Recent credit reform proposals would make control of credit subsidies the primary focus of budgetary efforts. By subjecting these subsidies to annual appropriations, the Government would gain more effective means to control the long-run fiscal effects of credit programs. Such reforms also would represent an important first step in improving their economic effects by eliminating unintended subsidies. However, many high subsidy-rate programs appear to have a significant effect on the allocation of credit without yielding clearcut efficiency gains.